Isolation and Characterization of a Flavonone From the Leaves of Sudanese Geigeria alata(Benth and Hook)- Asteraceae - Karim, M, Abdel; I, Mazen,; M.S, Khalid, (IJRDO - JOURNAL OF BIOLOGICAL SCIENCE, 2017)
Phytochemical screening of Geigeria alata leaves revealed the presence of flavonoids,tannins and alkaloids. A flavonoid - compound I- was isolated from ethanol extract by column and thin layer chromatography and its structure was established on the basis of its spectral data (IR, UV, NMR and MS). Compound I and different fractions (ethanol, chloroform, n- butanol and ethyl acetate) of Geigeria alata were screened for their antimicrobial activity against six standard human pathogens. The ethyl acetate fraction showed excellent antibacterial activity against all test organisms.However, the ethanol extract was inactive against the test bacteria ,but it gave good antifungal activity against Aspergillus niger The chloroform and n-butanol fractions exhibited moderate activity against Escherichia coli .